Effect of Braiding Angle on the Impact and Post-Impact Behavior of 3D Braided Composites - Yan, S.; Guo, L.Y.; Zhao, J.Y.; Lu, X.M.; Zeng, T.; Guo, Y.; Jiang, L. (Проблемы прочности, 2017)
In this study, the impact and post-impact behavior of three-dimensional (3D) four-directional carbon/epoxy braided composites having different braiding angles were investigated. The same impact energy (45 J) was applied to the specimens. The post-impact mechanical properties of the materials were performed by compression after impact (CAI) testing, and the processes were monitored by the acoustic emission (AE) technique. Results showed that the specimens with larger braiding angle sustained higher peak loads, and smaller impact damage area, mainly attributed to a more compact space arrangement. The CAI strength and damage mechanism were found to be mainly dependent on the axial support of the braiding fiber tows. Increasing the braiding angle of the composites, the CAI strength was reduced, and the damage mode of the composites was changed from transverse fracture to shear one. Combining AE parameters and CAI curves allows one to characterize the failure process, thereby enabling fracture analysis of the materials under study.